THE COMPUTERIZED ACCOUNTING AND INFORMATION TECHNOLOGY STUDENTS’ TRANSLATIONS VIEWED FROM SYSTEMIC FUNCTIONAL (English Education Journal, 2012)
Studi ini bertujuan untuk a) menggambarkan realisasi dari interpersonal meaning, experimental meaning, dan tekstual meaning pada translasi siswa jurusan CA dan IT STMIK WP, b) menjelaskan perbedaan dan persamaan antara translasi siswa CA dan IT dalam merealisasikan ketiga meaning tadi, c) menjelaskan apakah arti sudah tepat terhadap bahasa target. Penelitian ini merupakan penelitian qualitative, dengan siswa CA dan IT sebagai subjek. Data diambil dari hasil translasi siswa CA dan IT. Peneliti mengimplementasikan teoti SFL dan translasi. Hasil penilitian menunjukan persamaan terjadi pada hasil translasi kedua jurusan tersebut dalam ideational theme. Perbedaan  terjadi pada trasnitifitas dan interpersonal meaning pada proses quantitas. Translation equivalence di capai melalui translation shift.The study on translation viewed from SFL aims at a) describing the realization of interpersonal meaning, experiential meaning, and textual meaning in the students’ translations of CA department and IT students’ translations, STMIK WP, b) explaining the differences and the similarities between students’ translations of CA department and IT department at STMIK WP in realizing those three meanings c) explaining whether the meaning of the source language is equivalence to the target language. It is a qualitative research; CA students and IT students as the subjects of this research. The data of this study are taken from students’ translations on CA and IT department of STMIK WP in form of Indonesian-English translation. There are ten translations; five samples of each are selected to obtain the variation process of SFL realization In analyzing the data, I implemented SFL theory and the translation theory. The results showed that the similarities between both departments are occurred in experiential meaning and textual meaning. Many students used ideational theme. The differences between those departments are occurred in transitivity and interpersonal meaning on the quantity of the process. In terms of translation equivalence in this text, it is achieved through translation shift.